Breastfeeding Practices in Medical Nutrition Treatment of Phenylketonuria - Çakır Biçer, Nihan; Ersoy, Melike (My University, 2019)
Objective: Phenylketonuria (PKU) is an inherited metabolic disease with the increase of phenylalanine (phe) in the blood and body fluids in the absence of phenylalanine hydroxylase enzyme. PKU was the first inborn error of metabolism treated with medical nutrition therapy (MNT). The aim o f this study was to evaluate the breastfeeding practices in the MNT of PKU patients followed up at Dr. Sadi Konuk Training and Research Hospital, metabolism reference clinic for three years. Methods: Forty-two patients were reviewed for infants diagnosed with PKU between 2016 and 2019. Eighteen PKU patients (8 mild-PKU, 10 classic-PKU) over two years old and diagnosed with National Newborn Screening Program were included the study. MNT, blood phe, tyrosine (tyr) levels and anthropometric measurements of patients were evaluated retrospectively. Results: The mean age of patients is 2,5±0,4 years and 44% were male. The patients were diagnosed at a mean age of 13,7±6,7 days with blood phe and tyr levels of the patients were 1756 pmol/dL and 65 pmol/dL. After the diagnosis, 24-hour-BH4-loading test was applied, breastfeeding was interrupted until the blood phe level was <600 pmol/dL (mean 3,7±1,6 days) and breast milk was stored for reuse. In this process, MNT was applied phe-free medical formula with an average of 2,1 g/kg/day essential amino acid (eaa), 108 kcal/kg/day energy and 150 ml/kg/day fluid. After the blood phe level was <600 pmol/dL, free breastfeeding was initiated. Mean breastfeeding duration of patients was 17,8±9,3 moths. In the first 6 moths 0.9 g/kg/day eaa, 43 kcal/kg/day and 57 ml/kg/day fluid were applied and average blood phe and tyr levels were 240 pmol/dL and 70 pmol/dL. Complementary feeding education was given to all patients at 6 months. At the age of 6-12 months the patients received MNT containing average 0,9 g/kg/day eaa, 0,54 g/kg/day natural protein, 25 mg/kg/day phe, 74 kcal/kg/day energy and average blood phe and tyr levels were 314 pmol/dL and 69 pmol/dL. At the age of 12-24 months, the MNT containing average of 1,1 g/kg/day eaa, 1 g/kg/day natural protein, 26 mg/kg/day phe, 109 kcal/kg/day was recommended to patients and average blood phe and tyr levels were 312 pmol/dL and 82 pmol/dL and phe:tyr ratio was 3,8. Anthropometric measurements of the patients were observed to be within normal range during the study. Conclusion: Free breastfeeding is a successful and reliable practice that supports the healthy growth and development of the child in the life-long MNT of PKU.
Keywords: Breastfeeding; Phenylketonuria; Medical Nutrition Treatment